2021
DOI: 10.1038/s41598-021-85597-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corneal parameters, refractive error and age on density and morphology of the subbasal nerve plexus fibers in healthy adults

Abstract: The purpose of this study was to analyze corneal sub-basal nerve plexus (SBNP) density and morphology and their relationships with corneal parameters and refractive status. In this single center study, in vivo confocal microscopy (IVCM) was performed in 76 eyes of 38 healthy subjects aged 19–87 (mean age 34.987 ± 1.148). Nerve fiber analysis was performed using Confoscan 4 microscope with semi-automated software (Nidek Technologies, Italy) The nerve fiber length (NFL) µm/mm2, nerve fiber density (NFD) no./mm2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…19,20 On the other hand, some researchers revealed a correlation between corneal nerve density loss and age. [19][20][21] Therefore, we anticipated that the results of this study, which we intentionally screened from absolutely healthy subjects, limited the age range of participants and compared with those of age matched controls, can be generally applied as a standard baseline characteristic of corneal subbasal nerves to distinguish otherwise invisible abnormalities or degenerative nerve changes from normal nerve findings at each age. In turn, this may support the diagnosis and/or prognostication of some subclinical NK-related conditions and expedite the management of particular ocular and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 On the other hand, some researchers revealed a correlation between corneal nerve density loss and age. [19][20][21] Therefore, we anticipated that the results of this study, which we intentionally screened from absolutely healthy subjects, limited the age range of participants and compared with those of age matched controls, can be generally applied as a standard baseline characteristic of corneal subbasal nerves to distinguish otherwise invisible abnormalities or degenerative nerve changes from normal nerve findings at each age. In turn, this may support the diagnosis and/or prognostication of some subclinical NK-related conditions and expedite the management of particular ocular and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,42,53,54 However, some investigators have revealed contradictory results as they identified that significant nerve loss was related to increasing age. [19][20][21]23,55,56 These studies included subjects older than the age of 60, which was beyond the range of our study group. The rationale that we recruited subjects under 60 years old was to analyze the normal nerve characteristics and to preclude the results of nerve analysis affected from degenerative changes in the elderly.…”
mentioning
confidence: 99%
“…Confocal microscopy might be superior to specular microscopy to analyze the endothelial cells in AACC with corneal edema. The confocal microscope can directly obtain images of tissues and cells in each layer of the cornea through continuous confocal scanning, detecting various elements of normal and affected corneas in multiple layers and in vivo, without fixation and staining of tissue sections [9][10][11][12][13][14]. Thus, it is a major method for exploring the pathological mechanism of ophthalmic diseases at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy is a novel non-invasive corneal imaging examination method [9][10][11]. Due to high resolution and magnification, it reveals the corneal changes at the cellular level under three-dimensional space and real-time conditions; similar results could be obtained in the cloudy corneal tissue, making it a commonly used tool for the clinical study of corneal lesions [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation